2010
DOI: 10.1002/cyto.b.20555
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal B cell lymphocytosis: Clinical and population perspectives

Abstract: Monoclonal B Cell Lymphocytosis (MBL) refers to clones of CLL-like cells that exhibit CLL characteris-Five years after the formal description of monoclonal B cell lymphocytosis (MBL) as a uniform nomenclature for CLL-like cells clones that fall short of the numbers required for CLL diagnosis (1,2), the clinical, demographic and molecular features have begun to come into better focus. This report examines offers a clinical perspective on the controversies and suggests studies required for further progress. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In the majority of cases, the monoclonal B‐cells express a CLL‐like immunophenotype (2). The risk of progression varies according to the number of MBL cells and type of MBL (3) with approximately 1% per year risk of progression to CLL requiring treatment (4). The prevalence of MBL reportedly ranges from 3 to 5% (3,000–5,000 in 100,000) in the general population over the age of 50 years (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, the monoclonal B‐cells express a CLL‐like immunophenotype (2). The risk of progression varies according to the number of MBL cells and type of MBL (3) with approximately 1% per year risk of progression to CLL requiring treatment (4). The prevalence of MBL reportedly ranges from 3 to 5% (3,000–5,000 in 100,000) in the general population over the age of 50 years (5).…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of CLL-like MBL patients can be differentiated. A small fraction of MBL cases (~10%) are described as high-count MBL (hiMBL), being diagnosed during the characterization of otherwise asymptomatic lymphocytosis with a whole lymphocyte count over 3.5x10 9 /L [ 4 , 5 ]. It is assumed to be a precursor state of CLL, with a progression rate to CLL that requires treatment of ~1–2% per year [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…B-1 cells normally constitute only 5% of total B cells with the major fraction of these cells residing in the peritoneal cavity and a smaller fraction in the spleen. Recent evidence suggests that almost all cases of CLL are preceded by an asymptomatic precursor stage of monoclonal or pauci-clonal B cell lymphocytosis (<5x10 9 /l) termed MBL [ 4 , 5 ]. We have recently shown that NZB mice also exhibit this precursor MBL stage, further validating it as a true model for human CLL [ 6 ].…”
Section: Introductionmentioning
confidence: 99%